New methods for comparing literacy across populations: insights from the measurement of poverty - Kevin Denny (Institute for Fiscal Studies (IFS), 2000)
This paper exploits an unusual policy reform that had the effect of reducing the direct cost of schooling in Ireland in the late 1960s. This gave rise to an increased level of schooling but with effects that vary substantially across family background. This interaction of educational reform and family background generates a set of instrumental variables that are used to estimate the return to schooling allowing for the endogeneity of schooling. Using a standard Mincer type model we find a large and well-determined rate of return of around 12% which are substantially higher than the OLS estimates of around 7%.
Keywords: 330; Analphabetismus; Armut; Messung; OECD-Staaten